P3-S1.21 Non-culture based Neisseria gonorrhoeae antimicrobial resistance surveillance. (10th July 2011) - Goire, N; Freeman, K; Tapsall, J; Lambert, S; Nissen, M; Sloots, T; Whiley, D
Abstract : Background: Increased reliance on nucleic acid amplification tests for the diagnosis of gonorrhoea, and issues with transporting viable Neisseria gonorrhoeae (NG) isolates, particularly from remote regions, undermines bacterial-culture-based NG antimicrobial resistance (AMR) surveillance. In this study, we explored non-culture based NG AMR surveillance by developing and validating a real-time PCR assay for direct detection of penicillinase-producing NG (PPNG) in clinical samples. Methods: The PPNG-PCR assay was designed as an indirect marker of penicillinase activity, by targeting a region of sequence conserved across all NG plasmid types harbouring the β-lactamse gene, while not targeting the actual β-lactamase encoding sequence. The assay was evaluated using 118 characterised NG clinical isolates, and then applied to samples collected from the Australia's Northern Territory (years 2008–2009) where penicillin is still used for treatment. These comprised 214 NG-positive clinical samples from which N gonorrhoeae were isolated and phenotypic penicillinase results were available and an additional 209 samples that were positive by NG-PCR only. Results: The PPNG-PCR2 assay provided 100% sensitivity and 98.5% specificity compared to bacterial culture results for the detection of PPNG in clinical specimens. PPNG-PCR false-positive results, presumably due to cross reaction with unrelated bacterial species, were observed in four clinical samples but were distinguished on the basis of late cycle threshold values. A total of 15/423 (3.6%) samples were positive by PPNG-PCR. These data vary from phenotypic surveillance rates for this region (2.5%–2.9%). Conclusion: In tandem with phenotypic surveillance, the PPNG-PCR assay provides enhanced epidemiological surveillance of N gonorrhoeae penicillin resistance and is of particular relevance to regions where penicillin is still used to treat gonorrhoea. We are currently evaluating assays targeting NG chromosomally-mediated resistance mechanism to β-lactam antibiotics.